Clustering, competition, and spillover effects: Evidence from Cambodia - Sokty Chhair; Carol Newman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The potential benefits of the geographical clustering of economic activity have been well documented in the literature, yet there is little empirical evidence quantifying these effects in developing country contexts. This is surprising given the emphasis in industrial policy on productivity growth and the potential gains that could be made by facilitating cluster formation. It is also possible that for some firms there may be disadvantages associated with locating close to competitors, in particular if they sell to customers located in the same geographic area. These represent a large proportion of firms in developing country settings at the early stage of industrialization, where physical infrastructure is underdeveloped and there are a large number of informal and service sector firms that often exclusively rely on customers in local markets. Using data on the population of all firms in Cambodia we investigate the pattern of firm clustering and explore the extent to which it leads to productivity-enhancing effects. We focus on two channels, a competition and a spillover channel and investigate the types of firms that benefit or suffer as a result of geographical clustering. We find strong negative competition effects associated with clustering for formal and manufacturing firms. We find some evidence of productivity spillovers for informal firms and firms in the manufacturing sector but they are not of a large enough magnitude to outweigh the negative competition effects observed.
Keywords: D2; L2; L6; L8; O1; 330; clustering; productivity spillovers; competition effects; informal firms; Cambodia